2010
DOI: 10.1007/s00436-010-1829-7
|View full text |Cite
|
Sign up to set email alerts
|

Bioactivity of propolis from different geographical origins on Varroa destructor (Acari: Varroidae)

Abstract: Varroa destructor is an ectoparasitic mite that affects colonies of honey bee Apis mellifera worldwide. In the last years, substances of botanical origin have emerged as natural alternative acaricides to diminish the population levels of the mite. In the present work, the bioactivity of propolis from different geographical locations of Pampean region from Argentina on V. destructor was evaluated. Fourteen propolis samples were organoleptic and physicochemically characterized and, by means topical applications,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 27 publications
1
27
1
Order By: Relevance
“…Although there is evidence that propolis has activity against the parasitic mite Varroa destructor (Damiani et al, 2010;Garedew et al, 2002), the bioactivity of propolis was observed only in laboratory conditions and we did not note any effect of the propolis on Varroa levels in the field. The lack of a significant difference in the levels of Varroa mites in May between control and propolis envelope colonies was expected as all colonies received miticide treatment before the winter.…”
Section: Discussioncontrasting
confidence: 70%
“…Although there is evidence that propolis has activity against the parasitic mite Varroa destructor (Damiani et al, 2010;Garedew et al, 2002), the bioactivity of propolis was observed only in laboratory conditions and we did not note any effect of the propolis on Varroa levels in the field. The lack of a significant difference in the levels of Varroa mites in May between control and propolis envelope colonies was expected as all colonies received miticide treatment before the winter.…”
Section: Discussioncontrasting
confidence: 70%
“…In vivo assay Damiani et al 2010;Garedew et al 2002;Garedew et al 2003a Bee products for self-medication…”
Section: Resin and Propolismentioning
confidence: 99%
“…Feeding propolis ethanolic extracts to wax moth (Galleria mellonella ) larvae in in vivo assays reduced wax moth larval growth, survival and heat production with increasing propolis concentration (Eischen and Dietz 1987;Garedew et al 2004a;Johnson et al 1994). Topical application of propolis extracts on V. destructor in vivo in the honeybee colony resulted in narcotic and lethal effects on the mite, and again interfered negatively with the larval heat production (Damiani et al 2010;Garedew et al 2002Garedew et al , 2003a. Indeed, Simone-Finstrom and Spivak (2010) suggested a propolis treatment to reduce mature female mite production at the colony level.…”
Section: Resin and Propolismentioning
confidence: 99%
“…The sample was weighed, frozen, ground and stored at 4º C until use. For the experiment, a soft propolis extract was prepared according to Damiani et al (2010). A suspension was elaborated from the raw propolis and ethanol 70% at 1:9 (w/v) ratio, extracted at 60°C for 2 h, filtered and then evaporated at 40° C to obtain a soft extract free of ethanol.…”
Section: Methodsmentioning
confidence: 99%
“…Few works have studied the role played by these resins in the control and resistance to the diseases in honey bee colonies. Propolis has proven to be active against the main bee threats such as the bacterium Paenibacillus larvae (Antúnez et al, 2008;Bastos et al, 2008;Mihai et al, 2012), the fungus Ascosphaera apis (Wilson et al, 2015), and the mite Varroa destructor (Damiani et al, 2010). In colonies of Apis mellifera L. (Hymenoptera: Apidae), the propolis added into the nest environment modified the expression of immunerelated genes in the exposed worker bees (Simone, Evans, & Spivak, 2009).…”
Section: Introductionmentioning
confidence: 99%